THE EFFECT OF QUALITY OF PUBLIC GOVERNANCE, ACCOUNTABILITY, AND EFFECTIVENESS OF INTENTION TO PAY ZAKAT IN ZAKAT INSTITUTIONS WITH TRUST AS MODERATING VARIABLES - Ika Kartika Kusumawardani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The purpose of this study was to determine the effect of the quality of public governance, accountability, and effectiveness on the intentions of members of the Indonesian Chinese Islamic Association (PITI) in Yogyakarta in paying zakat at zakat institutions with trust as a moderating variable. This research uses a quantitative approach, purposive sampling method. The sample is PITI Yogyakarta members, amounting to 100 people. Data analysis uses interaction test or MRA (Moderated Regression Analysis). The results of the statistical calculations with moderation test show that the influence of the quality of public governance (X1), accountability (X2), and effectiveness (X3) contributed (influence) 84.4% of the trust variable (Z) and 86.6% of the intention variable of PITI members pay zakat (Y). The results of statistical calculations show that the quality of public governance does not have a significant effect on the variable of trust and the intention to pay zakat. While the accountability and effectiveness variables have a significant effect on the variable of trust and the intention to pay zakat. Overall, the quality of public governance, accountability, and effectiveness with trust as a moderating variable has a significant influence on the intention to pay zakat. Keywords: The quality of public governance, accountability, effectiveness, intention of PITI members to pay zakat at zakat institutions